Pengaruh Framing Effect Sebagai Determinan Escalation of Commitment Dalam Keputusan Investasi: Dampak dari Working Experiences - Muhammad Nur Yahya; Jen Surya (Jurnal Akuntansi, 2012)
The prior of research have shown that the framing effect is one of determinant in explaining decisions to escalate commitment to failing projects. However , have not considered whether experience moderates the framing effect on escalation of commitment. This study reports the results of an experiment in which the effect of decision frame of investment performance with negative feedback informatian on judgment to continue project of experienced subjects is compared to inexperienced subjects. Forty six Aceh experienced managers and forty seven accounting students participated in this experiment. Two conditions based on prospect theory (negative framing and positive framing) manipulated, and two conditions of business experience, crossed between subjects. The experiment reaffirms that decision frame does not have effect on judgment of experienced subject but those frame indeed have effect on judgment to continue project of inexperienced subjects. The result of this research suggest that framing effect as drawn from prospect theory is one of explanatory power of escalation of commitment, but it can not generalized to real-world business settings.